2021
DOI: 10.3389/fmars.2021.639309
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Dimensional Structure of Mediterranean Shallow Rocky Reefs: Use of Photogrammetry-Based Descriptors to Assess Its Influence on Associated Teleost Assemblages

Abstract: In the Mediterranean Sea, shallow rocky reefs and the associated three-dimensional (3D) structure support rich and abundant communities; they are therefore of functional importance, in particular for the renewal of fish stocks. However, these habitats and their functions are likely to be altered by anthropogenic pressures inducing habitat transformations. It is therefore necessary to assess their 3D structure, their transformations and relationship to communities, especially for management and conservation pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Importantly, SfM methodolgy conferred the additional advantage of only one tenth of the total data collection time occuring underwater. Monfort et al (2021) discussed similar findings where rugosity measured from SfM derived 3D point clouds was quicker than in situ 'chain and tape' measurements, while Couch et al (2021) found that photomosaics yeilded similar coral colony data to in situ data collection, but reduced field time by 55%. This reduction in field time is consistent with the use of other photographic techniques, such as photoquadrats, over field quadrats (Preskitt et al, 2004).…”
Section: Strengths and Limitationsmentioning
confidence: 61%
See 1 more Smart Citation
“…Importantly, SfM methodolgy conferred the additional advantage of only one tenth of the total data collection time occuring underwater. Monfort et al (2021) discussed similar findings where rugosity measured from SfM derived 3D point clouds was quicker than in situ 'chain and tape' measurements, while Couch et al (2021) found that photomosaics yeilded similar coral colony data to in situ data collection, but reduced field time by 55%. This reduction in field time is consistent with the use of other photographic techniques, such as photoquadrats, over field quadrats (Preskitt et al, 2004).…”
Section: Strengths and Limitationsmentioning
confidence: 61%
“…These non-rigid taxa will continuously move in relation to water motion which has the potential to hinder the SfM reconstruction process, as has been shown in terrestrial systems when surveying vegetation in windy conditions (Dandois et al, 2015;Fraser and Congalton, 2018). Diverbased SFM photogrammetry work on algal dominated rocky reefs has to date been limited in spatial scale and focussed on measuring a single metric such as reef rugosity (Monfort et al, 2021), substrate composition (Ternon et al, 2022) or quantifying crustose coralline algae cover underneath kelp canopies (Smale et al, 2020). The potential for using SfM photogrammetry for collecting data from temperate rocky reef ecosystems, particularly as an alternative to, or supplement to traditional SCUBA-based methods for benthic monitoring, requires further investigation.…”
Section: Introductionmentioning
confidence: 99%